Effect About Therapeutic Communication For· Stress Hospitalisation Response For Todller Children In Ag Range (1-3 Years Old) In Kertawijaya Room Dr. Wahidin Sudiro Husodo Hospital Mojokerto - Wahyuni, Lutfi (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractDuring the process, it can make the child having stress. One of therapy to less stress is therapeutic communication. Therapeutic communication decreases stress because communication has purpose to change clients behavior to get optimal health. Therapeutic communication has an important role to help a child to face his problem. The benefit of therapeutic communication for todller child is a child wants to receive or not to have a medical act. The purpose of this research is to prove there is an effect or not of therapeutic communication for responses about hospitalisation stress. This research uses one group pre test post test design. The population of this research is 22 participants and the way to take samplings consecutive sampling and the researcher gets 22 participants who has hospitalisation stress. The instrument of this research is observation sheet which is completed with 15 questions. The result of wilcoxon signed ranks test uses SPSS type 16.0 which has known p Value (O,OOO)<a (0,05) and the researcher gets result before they are given therapeutic communication is 14 children which have protest reponses and after they are given therapeutic communication, 11 children have give up responses. The result of this research shown that there is an effect about therapeutic communication for stress hospitalisation response for todller children in ag range (l ·3 years old) in kcrtawijaya room Dr. Wahidin Sudirohusodo hospital. Therapeutic communication is an effective way to decrease hospitalisation stress but for participabts who have given therapeutic communication but they do not get decrease stress,it is caused because stress factors which has received still dangerous.Keyword: Therapeutic Communication, Stress hospitalisation, Todller